An experimental investigation of fractional flow reserve of human coronary artery - Herald, Kinston John (Nanyang Technological University, 2023)
Aortic valve stenosis is a type of heart valve disease and can be severe if not detected on time. This happens when the valve between the lower left heart chamber and the aorta is narrowed. Volume of blood flow is restricted from the heart to the aorta and to the rest of the body which may eventually lead to death. There are numerous ways to diagnose aortic valve stenosis. Methods such as Electrocardiogram (ECG or EKG), Echocardiogram, computerized tomography (CT) coronary angiography may help to determine the condition’s severity but may not be suitable for certain patients.